The Filipinization of Coca-Cola television advertisements - Co, Christine Darcy Roumayne Torralba 1979-
Coca-Cola has been in the Philippines since 1927. Since then, The Coca-Cola Company has become one of the leading businesses in the country. The success of the industry thrives in a mutual understanding between the Company and the Filipinos. Marketing investments enhance consumer preference. Advertisements give compelling reasons to consumers why they should patronize Coca-Cola. For Coca-Cola, effective advertising is innovative, refreshing, relevant, and real. The Company believes that one will never be the real thing, if one is out of touch. Thus, Coca-Cola was built-up to be something that is always within reach of the Filipinos. This study is a qualitative research on the filipinization process of Coca-Cola television advertisements. It deals with how Coke commercials from 1990, the start of the Can't beat the real thing campaign of Coca-Cola, until the present Coca-Cola Enjoy campaign, have been patterned to best appeal to the Filipinos. Data was gathers through content analysis of Coca-Cola advertisements from 1990-2000, and focus interviews with people from the Coca-Cola Company and McCann-Erickson who directly involved with the conceptualization and production of Coca-Cola advertisements. Findings of the study revealed that in 72 years of Coca-Cola existence in the Philippines, advertisers have experimented with different advertising strategies. During the first year of filipinization in 1990, advertisers used celebrity endorsers in advertisements for name association. In 1993 when computers were the trend, advertisers came out with computer-enhanced advertisements. It was only 1998 when Coca-Cola advertisements went purely local. This was brought about by the tremendous success of the "Heaven" commercial the previous year. Informants agree that the audience is as important as the over all message in the conceptualization of Coca-Cola advertisements. Advertisers are always mindful of what the consumers want in order to stay relevant in their lives. It is this constant search for relevance that brought about the changes in Coca-Cola campaigns. Throughout the years, Coca-Cola advertisements have connected in a very special way with the Filipinos. For not only do the commercials present Coca-Cola in the most positive light, it situates the brand amidst the everyday existence of the consumers. In effect, not only is Coca-Cola seen as the best soft drink in town, it is also accepted as the drink that embodies Filipino culture. After years of conditioning, Filipinos have come to associate Coca-Cola with their fondest memories. Whenever they see a Coke advertisement, they begin to see themselves in the commercials. Through the course of time, there might come products that have extreme likeness with Coca-Cola, there might even be some of that claim to be better that Coca-Cola, but consumers will still prefer Coca-Cola over the other brands, because no matter what happens, the special moments, the many firsts, and the unforgettable experiences, that Filipinos haveshared with Coca-Cola can never be duplicated.